A river of disease: Silicosis and the future of class actions in South Africa. Issue 1 (2nd January 2021) - Brickhill, Jason
Abstract: Silicosis is an incurable lung disease caused by the inhalation of silica dust. Gold is usually found alongside silica, so goldminers are especially at risk of silicosis. Studies show that up to a quarter of career mineworkers in South Africa have contracted it. As one expert witness in the litigation put it, a 'river of disease' was flowing through the mines. The river metaphor also captures the meandering course of the silicosis litigation, which spanned more than a decade, its course unpredictable, joined by new tributaries and splitting into new streams of litigation along the way. It included test cases, arbitration, massed claims and eventually, a class action. The silicosis class action in South Africa not only provided the first real test for the new court-made rules governing class actions, but is one of the largest and most complex multi-class, multi-defendant, dispersed incident class actions the world has seen. The class action succeeded, culminating in a R5 billion settlement. It also provides a strong basis to consider how best class action law should develop in South Africa. This article engages with the test for certification, representation in class actions, settlements and legal fees and costs. It argues that the constitutional commitment to access to justice undergirds class actions and must inform the development of these rules. The profit incentive presented by class actions presents risks of abuse that must be addressed. The Constitution, and not the market, should determine which poor litigants get legal representation to bring class actions, and how class actions work.